Peculiarities of rendering of material in virtual computers' network course - Kaklauskas, Liudvikas (Lietuvos matematikos rinkinys, 2004)
Problems of singling out the most important themes of distance computers' network course are analyzed in the present article. After an expert survey is carried out we pursue to find out which themes are the most relevant for students. Means, possibilities of their usage, according to selected topical themes, for rendering of course in virtual medium of Learning Space are analyzed. Worksheet for this course and problems of their selection are reviewed.
Keywords: analysis of documents; distance learning; interaction